Designing Healthcare and Pharmaceutical Applications Based on Geographic Information Systems (GIS) - Erlin,; Ramalia Noratama Putri,; Wibowo, M Teguh (JIM - Journal International Multidisciplinary, 2023)
Data and information pertaining to health care delivery that have been disclosed at this time will be documented and ultimately used as input to get input, output, and output research processes. Utilizing a mobile device, the provided application can make it easier for users to do location-based searches and access remote healthcare services. Sample data from locations providing health care and other information are required for this application in order to make it simple for the general public to get accurate information. The application presents a list menu of health services based on the database category. The application may display a map of Pekanbaru’s as well as coordinate points for every data in the database. This application provides information to the people of Pekanbaru’s about health-care facilities, such as pharmacy, clinics, and hospitals. The information and data that will be disseminated will make it easier for users to find locations that match their needs or are close to where they are since they are categorized by proximity to the location. This app provides information on the routes that are being used to go to the locations that have been selected. This application is useful for increasing the availability of health-care information to those who require it.